2019
DOI: 10.3390/f11010007
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interactions between Invasive Fusarium circinatum and Other Pine Pathogens in Europe

Abstract: Pines are major components of native forests and plantations in Europe, where they have both economic significance and an important ecological role. Diseases of pines are mainly caused by fungal and oomycete pathogens, and can significantly reduce the survival, vigor, and yield of both individual trees and entire stands or plantations. Pine pitch canker (PPC), caused by Fusarium circinatum (Nirenberg and O’Donnell), is among the most devastating pine diseases in the world, and is an example of an emergent inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 232 publications
(321 reference statements)
0
23
0
Order By: Relevance
“…In fact, D. sapinea, S. polyspora and other fungi were also present in some of the sampled symptomatic material (data not shown). Diverse authors also report more than one species involved in dieback and blight diseases, including pestalotioid species and other fungi [8,[45][46][47] and observed that some abiotic factors also have a major role in disease development, namely water stress and air temperature [41,42,47]. In this case, a synergic effect among Pe.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, D. sapinea, S. polyspora and other fungi were also present in some of the sampled symptomatic material (data not shown). Diverse authors also report more than one species involved in dieback and blight diseases, including pestalotioid species and other fungi [8,[45][46][47] and observed that some abiotic factors also have a major role in disease development, namely water stress and air temperature [41,42,47]. In this case, a synergic effect among Pe.…”
Section: Discussionmentioning
confidence: 98%
“…Neofusicoccum parvum is a generalist, cosmopolitan pathogen, occurring in various environments with a temperate, Mediterranean, or subtropical climate. The host range of this species encompasses at least 90 botanical entities, especially woody angiosperms, including conifers and many horticultural plants [ 4 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In association with other fungal pathogens, including other Botryosphaeriaceae species, N. parvum is involved in the trunk disease complex of grapevine, also known as Botryosphaeria dieback, and is regarded as one of the most aggressive causal agent of this disease, which is responsible for severe economic losses in vineyards worldwide [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In nine countries, only visual inspection of symptoms in the field or morphological diagnosis of cultures in the laboratory was used to confirm pathogen absence or presence. However, visual inspection alone may not be sufficiently reliable for F. circinatum detection and identification because the fungus may behave as an endophyte or latent pathogen with no visible external symptoms or it can be mistaken for other pathogens that cause similar symptoms [7,47,48]. It is preferable, therefore, to combine visual surveys with molecular detection methods for reliable and more precise identification [46,49,50].…”
Section: Europementioning
confidence: 99%